Structural Changes of Intermetallic Catalysts under Reaction Conditions. Issue 8 (13th August 2021) - Li, Xiao; Zhao, Jianxiong; Su, Dong
Abstract : Intermetallic Catalysts Intermetallics with long‐range chemical ordering have been demonstrated to be excellent catalysts in many reactions. Their surface structures under real reaction conditions are crucial for understanding the catalytic mechanisms. In article number 2100011 by Xiao Li, Jianxiong Zhao and Dong Su, the structural changes of intermetallic catalysts under reaction conditions are systematically discussed. Strategies to improve the activity and durability of catalysts are also presented.